1996
DOI: 10.1515/text.1.1996.16.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and discourse

Abstract: Emotions have increasingly become the object of systematic sociological inquiry. Due to their special nature, a number of methodological problems accrue to the task of making emotions accessible to analysis. This article presents the results of an inquiry into the ways in which emotions are expressed in narratives and conversation. Conversations involving positive and negative self-feelings are analyzed in regard to paralinguistic markers. These markers are presented and discussed, and the ways in which marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…People in a happy mood may underestimate the likelihood of offending others and use more direct and less polite request strategies (e.g., Bless, Mackie, and Schwarz 1992;Forgas 1995;Worth 1989, 1991;Sinclair and Mark 1992). Also, receivers in a positive mood expect higher assertiveness and lower politeness, because of loosened perceptions of social rules and frames (Bloch 1996;Forgas 1999aForgas , 1999b. Overall therefore, when in a positive mood, both sources and receivers of a communication are predisposed to use and accept assertive language.…”
Section: Assertive Language Communication Expectations and Complianmentioning
confidence: 99%
See 1 more Smart Citation
“…People in a happy mood may underestimate the likelihood of offending others and use more direct and less polite request strategies (e.g., Bless, Mackie, and Schwarz 1992;Forgas 1995;Worth 1989, 1991;Sinclair and Mark 1992). Also, receivers in a positive mood expect higher assertiveness and lower politeness, because of loosened perceptions of social rules and frames (Bloch 1996;Forgas 1999aForgas , 1999b. Overall therefore, when in a positive mood, both sources and receivers of a communication are predisposed to use and accept assertive language.…”
Section: Assertive Language Communication Expectations and Complianmentioning
confidence: 99%
“…pect to be addressed with more direct and assertive language (Bloch 1996;Forgas 1999aForgas , 1999b. This matching pattern appears consistent with language behavior literature, which demonstrates that higher compliance occurs when the language of requests fits the receiver's expectations (e.g., Brown and Levinson 1987;Forgas 1998).…”
mentioning
confidence: 99%
“…He has found people in a negative mood to be more careful, and to formulate more polite and elaborate requests, whereas people in a positive mood were more direct and less elaborate in formulating requests. Bloch (1996) also shows that positive emotions are expressed in a more direct language. Research has further found that happier people are more prepared for bold actions and decisions (e.g., Qiu and Yeung 2008).…”
Section: The Role Of Hedonic Context and Framingmentioning
confidence: 91%
“…And so, for Chafe, laughter ''expresses a feeling that insulates us from serious thought and action'' (p. 145). But the research of Bloch (1996;cited in Tracy, 2002, p. 88 f.), in addition to the research mentioned above, seems to negate such insulation. Bloch has dealt with very real everyday narrative situations of her Danish subjects, and her findings have indicated that laughter overlaid on speech may carry either the positive meaning of joy or the negative meaning of shame.…”
Section: Chafe (2007)mentioning
confidence: 92%